The Frequency of Blood Transfusion Reactions: A Retrospective Study from a Tertiary Care Hospital: Frequency of Blood Transfusion Reactions - Chohan, Uzma; Najam, Sumayya; Rajput, Khushbakhat Khanzada; Rajput, Maryam Khanzada; Waqar, Syeda Azka; Yunus, Namra (Pakistan Journal of Health Sciences, 2025)
Blood Transfusion Reactions (BTRs) are complications that may occur during or after transfusion, in which allergic reactions and Febrile Non-Hemolytic Transfusion Reactions (FNHTRs) being the most common. Objective: To assess the frequency and types of transfusion reactions among patients at Shahida Islam Medical College Hospital and a blood transfusion service supplier. Methods: This study analyzed transfusion reactions reported between January, 2022, and September, 2024. A total 1936 transfused has done during this time frame. Data were collected using non-probability convenience sampling, covering patient demographics, blood products used, and Incident rate of transfusion reactions. IBM SPSS version 28.0 was utilized for statistical analysis, with categorical variables presented as frequencies and percentages. Results: Out of 1936 transfusions a total 12 (0.6%) reported transfusion reactions in which allergic reactions accounted for the majority (50.0%), followed by FNHTRs (33.33%) and none or very limited reactions of other reactions seen both on whole blood and PCV. The overall incidence of transfusion reactions was 0.53%. Conclusions: This study highlighted that allergic reactions are the most prevalent Blood Transfusion Reactions, emphasizing the need for premedication protocols for high-risk patients. Future research should focus on identifying predictive markers for allergic reactions, refining transfusion protocols.